Monitoring of groundwater storage changes using the Gravity Recovery and Climate Experiment (GRACE) satellite mission: a case study of Sragen Regency, Indonesia - Moneer Hilal, Najm Al-Deen; Komariah; Handono Ramelan, Ari; Noda, Keigo (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Problem Statement and Purpose. Groundwater is an important resource for agriculture, drinking water, and ecosystems in Sragen Regency, Central Java, Indonesia. However, the area is significantly water-stressed due to recurrent droughts, pollution, and unsustainable extraction methods. The aim of this study is to monitor the changes of groundwater storages during 2003-2024 using Gravity Recovery and Climate Experiment (GRACE) satellite mission and Global Land Data Assimilation System (GLDAS) products into Google Earth Engine (GEE) to advance Sustainable Development Goal 6 (Clean Water and Sanitation) and SDG 13 (Climate Action).Data and Method. The study employs GRACE data to analyze Total Water Storage (TWS) and the hydrological components -Soil Moisture SM and Snow Water Equivalent SWE- that GLDAS provides as a supplement. Merging these datasets within GEE seeks to understand groundwater trends from seasonal to long-term.Result and Discussion. The study observed an average decrease in groundwater storage, with observed stresses during drier-than-usual periods in 2015-2016 and 2018-2020. Whereas, contrary to this long-term declining trend, the groundwater generally rises during wet seasons and falls again during dry seasons, demonstrating seasonality in storage. Furthermore, quantitative analysis revealed a net groundwater storage decline of approximately 15-20% during the 2003-2024 period, with critical depletion phases correlating with events (2015-2016) and prolonged droughts (2018-2020). The GRACE-GLDAS-GEE integration demonstrated high efficacy in detecting seasonal recharge cycles (+8-12 cm equivalent water height during monsoon months) versus dry-season depletion (-10-15 cm), providing unprecedented spatial-temporal resolution for this tropical agricultural region. This approach offers a scalable model for implementing SDG 6.4 (sustainable water withdrawals) through precision aquifer management in developing economies facing climate stress. The results should hasten the consideration of better water management approaches to stop further depletion of groundwater through methods such as managed aquifer recharge and maximizing irrigation efficiencies. This study provides a good example of using GRACE and GLDAS data adoption for regional groundwater monitoring, thus setting a solid basis for interventions aimed at alleviating water scarcity for Sragen Regency and beyond. This information will also serve as input in making decision-supporting management, aligning with SDG 6 targets for sustainable freshwater resource allocation and addressing challenges posed by climate variability and increasing anthropogenic pressures under SDG 13.